A compact wide‐band antipodal Vivaldi antenna design. Issue 4 (29th October 2018) - Zhang, Xiaoyan; Chen, Yuting; Tian, Miao; Liu, Jun; Liu, Haiwen
Abstract: A compact wide‐band antipodal Vivaldi antenna (AVA) is designed in this work. First, the traditional exponentially tapered edge of the radiator is replaced by an arc curve that makes the AVA compact. Second, the AVA is loaded with a "director" and a "convex lens" that improve its high‐frequency performance. The proposed antenna is fabricated and its dimensions measured. It occupies a small volume of 34 × 16 × 0.8 mm 3 and provides an operating frequency range from 3.01 to 10.6 GHz with a higher gain in the low frequency region than that of reference antennas. The measured results perfectly coincide with the simulated ones, which demonstrates the feasibility of the novel AVA design.